High-dose intravenous immunoglobulins for the treatment of dermatological autoimmune diseases - Hoffmann, Jochen; Enk, Alexander (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Summary: Based on their immunomodulatory properties, high-dose intravenous immunoglobulins (IVIGs) are successfully used in the treatment of various dermatological autoimmune diseases, in particular pemphigus vulgaris and dermatomyositis. In autoimmune bullous diseases, IVIGs can be used in an adjuvant setting (second- or third-line therapy) once combined immunosuppressive regimens have failed. In dermatomyositis, IVIGs may already be employed as an adjuvant second-line therapy after failure of corticosteroid monotherapy. In scleromyxedema, IVIGs may be considered as first-line treatment, given the lack of effective and safe alternatives. Other potential indications for IVIGs may include severe recalcitrant cases of systemic vasculitis and systemic lupus erythematosus. Toxic epidermal necrolysis may be an indication for high-dose IVIGs if administered early. Common, readily manageable side effects include nausea, headache, fatigue, and febrile infusion reactions. Severe adverse events such as thromboembolic events, anaphylaxis, and acute renal failure are very uncommon. The risk of viral transmission is very low. Potential mechanisms of action include upregulation of inhibitory Fc receptors, reduction of the half-life of endogenous immunoglobulins due to displacement from protective receptor sites, neutralization of autoantibodies by anti-idiotypic antibodies, as well as inhibition of complement activation.
First published: 11 December 2017
Gesehen am 27.06.2018